Pembaharuan Hukum Keluarga di Somalia - Husin, Roihanah; Amatul Jadidah (MAQASHID, 2018)
The reformation of family law in Somalia, which is mostly Moslem populated and Syafi’ian in fiqh, greatly affected by Its social and political constellation. The colonialization of Britain and Italy, Its political and ideological affiliation to the Soviet Union during the cold war, as well as the dictator government for about 3 decades in after Its independence. In the development, those factors have revoked the family code reformation to its traditional roots there namely some parts of customery law and Syafi’ian Islam in fiqh. Such a detachment os Islamic law tradition had evoked a long serious conflict between the government and the society, particularly the Islamic scholars. This conflict even took a toll.